Chapter In situ rare long term observations of the dogtooth grouper Epinephelus Caninus in artificial reefs recently immersed in the National Park of the Calanques (north-western Mediterranean sea, France) - Perrot, Martin (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
On 2017, artificial reefs (ARs) targeting apex rocky species such as groupers were immersed in the National Park of the Calanques as part of an experimental ecological restoration project (REXCOR). The objective of the project is to evaluate the capacity of innovative designs of ARs to restore altered ecological functions impacted by the sewage outflow of the city of Marseilles. In 2018, one specimen of the dogtooth grouper, Epinephelus caninus, was observed during 7 months inside the ARs. Such a long-term site fidelity suggets that this urban area can shelter again high trophic level species.